2021
DOI: 10.1186/s12893-021-01310-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of lumen-apposing metal stents (LAMS) in the management of gastro jejunostomy stricture following Roux-en-Y Gastric Bypass for obesity: a prospective series

Abstract: Background Chronic strictures following Roux-en-Y Gastric Bypass (RYGB) are a troublesome complication that can lead to significant morbidity. The use of stents has been described but the need for X-ray and risk of migration have meant limited use in the management of these strictures. Lumen apposing metal stents (LAMS) have traditionally been used for management of pancreatic pseudocysts. They don’t require X-ray and are easy to deploy with a short learning curve. This paper explores the use o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…A 15×10-mm LAMS was the most commonly used stent, with median stent dwell time varying from 60-119 days. Our study quality assessment found that 11 were of medium quality [ 14 - 18 , 21 , 22 , 24 , 26 - 28 ] and 7 were of low quality [ 11 - 13 , 19 , 20 , 23 , 25 ] ( ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 15×10-mm LAMS was the most commonly used stent, with median stent dwell time varying from 60-119 days. Our study quality assessment found that 11 were of medium quality [ 14 - 18 , 21 , 22 , 24 , 26 - 28 ] and 7 were of low quality [ 11 - 13 , 19 , 20 , 23 , 25 ] ( ).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows the baseline characteristics of the included studies. The majority of the studies were from the USA, and only 2 studies were prospective [ 11 , 25 ]. Tables 2 and 3 summarize the clinical characteristics and clinical outcomes of the included studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Inflammation and healing of marginal ulceration at the gastrojejunal anastomosis (GJA) lead to granulation and scar tissue formation, culminating in late-onset anastomotic stenosis [23][24][25]69] . Sundaresan et al [69] observed higher stenosis rates with a 25 mm circular stapler compared to linear and robotic hand-sewn methods.…”
Section: Gastrojejunal Anastomotic Stenosismentioning
confidence: 99%
“…Inflammation and healing of marginal ulceration at the gastrojejunal anastomosis (GJA) lead to granulation and scar tissue formation, culminating in late-onset anastomotic stenosis [23][24][25]69] . Sundaresan et al [69] observed higher stenosis rates with a 25 mm circular stapler compared to linear and robotic hand-sewn methods. Stricture rates were 4.9%, 0.5%, and 1.2% for circular stapler, linear, and hand-sewn anastomoses, respectively, with circular stapler showing significant differences compared to linear stapler (P < 0.05).…”
Section: Gastrojejunal Anastomotic Stenosismentioning
confidence: 99%
“…Endoscopic balloon dilation has been demonstrated to be safe and effective for gastrojejunal strictures post-RYGB [93]. RYGB-associated strictures may also be safely treated with lumen-apposing metal stents (LAMS) [94][95][96]. In a prospective study of 412 patients who underwent RYGB, 14 patients developed a stricture, of which 12 had resolution of their stricture following LAMS insertion [94].…”
Section: Management and Treatment Approach To Gerd Following Bariatri...mentioning
confidence: 99%